Delving into the Essence of Matter through the Lens of the Electron Microscope - Chang, Hye Jung (2023 한국세라믹학회 추계학술대회, 2023)
One of the motive powers of the nanoscience development is availability of new instruments able to “see” and "control" at this scale. Currently, there are a large number of instruments that help scientists in the nano realm. Among them electron microscopy can be considered as the most powerful tool because it exhibits best spatial resolution (down to 0.5 Å) which is enough to resolve the individual atoms in a structure. Combined with complementary instruments, it produces various kinds of information of materials such as atomic crystal structure as well as chemical stoichiometry, electronic bonding, structural defects, magnetic structure and etc. Thus, electron microscopy is essential characterization tool for scientists who want to fabricate and deal nanomaterials. In this talk, I aim to introduce a case study that explores how the electrochemical properties of SOEC, the promising next-generation renewable energy technology, were elucidated through the lens of the microscope. Achieving continuous operation of the SOEC is a challenge due to the rapid delamination and degradation of the air electrode, which is not observed during the operation of solid oxide fuel cells. Delamination often leads to instantaneous catastrophic failure, making it challenging to obtain systematic information after complete failure. Here, we revealed how mechanical deformation and defects resulting from localized oxygen accumulation at the interface between the electrolyte and air electrode by various electron microscopy techniques including SEM, EPMA, FIB, precession electron diffraction in TEM, diffraction pattern analysis, and high-resolution TEM imaging, impair the electrochemical properties. By utilizing these integrated cutting-edge analysis methods, we were able to suggest a systematic degradation mechanism explaining how ions, lattice structure, nano-defects, and micro-sized cracks are interconnected, which differs from previous research